PENTINGNYA BELAJAR BAHASA INGGRIS UNTUK ANAK USIA SEKOLAH DASAR DI LINGKUNGAN RT 37 RW 13 KELURAHAN GIWANGAN KECAMATAN UMBULHARJO - Bernadetta Eko Putranti; Suprih Ambawani (DHARMA BAKTI, 2019)
English is a foreign language that is used as the language of communication throughout the world. The latest information on science, technology, politics, education, health and business as well as other fields of information are mostly written in a foreign language, especially in English. The problem gave us an idea to carry out community service in the neighborhood of RT / RW: 37/13, Giwangan, Umbulharjo, Yogyakarta. We did this community service to provide socialization about the importance of learning English for elementary school children to the PKK group in the environment. The community service carried out in the neighborhood of RT / RW: 37/13, Giwangan, Umbulharjo, Yogyakarta aims to make mothers (especially) begin to sort out and choose what method they will take to meet the needs of their children in learning English and prepare them in facing the progress and demands of the world today. The activity is carried out by socializing ways and alternatives that can be taken so that children can learn English well. This activity was attended by women members of the PKK and local RT administrators. They asked a lot of questions, and from the results of the discussion several ideas emerged to implement English learning for children in the RT / RW environment: 37/13, Giwangan, Umbulharjo, Yogyakarta. This activity is expected to provide alternative methods of learning English for children.